A Comparison of the Uptake of Two Research Models in Mobile Learning: The FRAME Model and the 3-Level Evaluation Framework - Marguerite Koole; Rosemary Buck; Kerry Anderson; Drea Laj (MDPI AG, 2018)
This paper discusses the diffusion of two models of mobile learning within the educational research literature: The Framework for the Rational Analysis of Mobile Learning (FRAME) model and the 3-Level Evaluation Framework (3-LEF). The main purpose is to analyse how the two models, now over 10 years old, have been referenced in the literature and applied in research. The authors conducted a systematic review of publications that referenced the seminal papers that originally introduced the models. The research team summarized the publications by recording the abstracts and documenting how the models were cited, described, interpreted, selected, rejected, and/or modified. The summaries were then coded according to criteria such as fields of study, reasons for use, criticisms and modifications. In total, 208 publications referencing the FRAME model and 97 publications referencing the 3-LEF were included. Of these, 55 publications applied the FRAME model and 10 applied the 3-LEF in research projects. The paper concludes that these two models/frameworks were likely chosen for reasons other than philosophical commensurability. Additional studies of the uptake of other mobile learning models is recommended in order to develop an understanding of how mobile learning, as a field, is progressing theoretically.